The Extremism Industry: A Political Logic of Post-Hegemonic Liberalism. (November 2020) - el-Ojeili, Chamsy; Taylor, Dylan
The rising fortunes of the academic 'extremism industry' call for robust social scientific scrutiny. We contend this industry is a significant expression of our current moment of post-hegemonic liberalism. We set out the typical definitional devices found in the literature, which assemble 'extremism' as a syndrome consisting of six major elements: non-normative values, anti-democracy, anti-liberalism, utopianism and a war on the present, totalisation and abstraction, justifications of unlawfulness. The extremism industry can be approached by way of three investigative spaces: modernisation approaches, psychological and culturalist explanations, and security and policing approaches. Within these spaces, we outline five ideal-typical modes of explaining extremism: consensual anti-fascism, civilisational provincialism, folk secularism, psychologistic pathologisation and moral educationism. We maintain that the extremism industry is analytically weak and politically pernicious and suggest that what passes for 'extremism' is better situated and understood at the crossroad of three important vectors: intellectual, geo-political and world-economic.